Cranial sonography in extremely preterm infants. Issue 5 (28th February 2014) - Pekcevik, Yeliz; Ozer, Esra Arun; Guleryuz, Handan
ABSTRACT Survival rates of extremely preterm infants have risen dramatically, paralleling improvements in prenatal and neonatal care. Cranial sonography is the primary imaging technique for the evaluation of brain injury in these patients. Extremely preterm infants have some unique features related to ongoing maturation, and associated findings on cranial sonography should be considered for accurate and early diagnosis. The aim of this pictorial essay is to illustrate normal anatomy, normal variants, and pitfalls that lead to misinterpretation of cranial sonography in extremely preterm infants. © 2014 Wiley Periodicals, Inc. J Clin Ultrasound42:283–290, 2014